Assessment of speech and language delay among 0-3 years old children attending well-baby clinics using Language Evaluation Scale Trivandrum - Kondekar, Santosh Venketraman; Shree, V Sudha (Indian Journal of Child Health, 2016)
Objectives: To assess the prevalence of language delay in children aged 0-3 years and to evaluate the association of sociodemographic, perinatal, and home environment factors with language delay. Materials and Methods: A total of 200 children aged 0-3 years attending the well-baby clinic or the outpatient department were included in the study, with exclusion of children with severe illnesses or those with known developmental delays. The parents of the children were asked to fill a risk factor analysis questionnaire consisting of questions related to the socio-demographic, perinatal factors, and home environment. Children were screened for developmental delay using Language Evaluation Scale Trivandrum for children aged 0-3 years. Results: Prevalence of language delay in our study was 13%. Positive home environment was significantly associated with no language delay in children (p=0.0481); the association was also seen with the parental habit of reading and the happy nature of children (p